2016
DOI: 10.1111/pops.12347
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Political Ideology: A First Global Assessment

Abstract: This article presents the first assessment of how the five-factor model of personality and political ideology are associated across the world. Personality traits become more and more important in the study of political behavior. And the relationship with ideology virtually parallels the history of this line of research. Yet, many existing studies are limited to single, highly developed countries and mostly draw on nonrandom or nonrepresentative samples. Our study, in contrasts, makes use of the most recent wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 53 publications
7
107
1
1
Order By: Relevance
“…For example, Gerber et al () found that Conscientiousness was associated with both social and economic conservatism, though its relationship with social attitudes was slightly stronger. And Clifford et al () found that Conscientiousness predicted both social and economic conservatism in their American datasets, while Fatke () found a similar result in the cross‐national data he examined.…”
Section: The Psychological Bases Of Political Preferencesmentioning
confidence: 87%
See 1 more Smart Citation
“…For example, Gerber et al () found that Conscientiousness was associated with both social and economic conservatism, though its relationship with social attitudes was slightly stronger. And Clifford et al () found that Conscientiousness predicted both social and economic conservatism in their American datasets, while Fatke () found a similar result in the cross‐national data he examined.…”
Section: The Psychological Bases Of Political Preferencesmentioning
confidence: 87%
“…Yilmaz &Saribay (, Study 2) found the same thing using a Turkish student sample. Similarly, using cross‐national data spanning 21 nations, Fatke () found that Openness predicted liberal social attitudes (though only in democratic countries) but was unrelated to economic attitudes (although see Ludeke & Larsen, ). However, other studies provide evidence for symmetry.…”
Section: The Psychological Bases Of Political Preferencesmentioning
confidence: 97%
“…AlthoughFatke (2017) also found, using data from the World Value Survey, that the relationship between Big Five personality traits and political orientation differs widely across 21 countries, the quality of the personality data included in the World Value Survey has been called into serious question(Ludeke & Larsen, 2017).…”
mentioning
confidence: 99%
“…However, since the TIPI only consists of two items per scale, the inter‐item correlations are lower than for more homogenous scales (Gosling et al , 516). The inter‐item correlations might also differ between studies, which may be attributable to the use of different adjectives or to studies being conducted in different countries and cultures (Ha et al ; Fatke ; Weinschenk ). Weinschenk () compared inter‐item correlations in different studies and concluded that the correlation for Agreeableness is the most varying.…”
Section: Methods and Datamentioning
confidence: 99%
“…The effect of personality is often comparable to that of demographic variables such as education, class, race and income. After controlling for other factors, personality thus exerts a significant influence on, for example, political ideology, political preferences, partisanship, voter turnout, civic engagement and attending political meetings (Caprara et al ; Mondak & Halperin ; Ha et al ; Fatke ; Weinschenk ). Specific findings vary across studies due to sampling variations, measurement variations and historical, cultural and political context (Ha et al , 513).…”
Section: Personality Traits and Political Behaviourmentioning
confidence: 99%